Considerations for the placement of dental implants in patients with idiopathic osteosclerosis. A review of the literature - Chunga Cobeña, Gerardo Martín (2019)
This research carried out a review on the placement of dental implants in patients with idiopathic osteosclerosis, for which some researchers propose that a specific protocol should be taken into account, which speaks of drilling with external irrigation with physiological saline at 5 °C. The stability of the dental implant is important for good osseointegration, which depends on the bone quality, the surgical technique, and the contact surface between bone and implant. The torque force for good primary stability, according to a systematic review, is 20 Ncm to 45 Ncm. For the successful placement of dental implants, it is necessary to have a good diagnosis of the edentulous area and correct osseointegration. The correct identification of clinical findings, such as idiopathic osteosclerosis, is important to differentiate it from other benign and malignant bone pathologies. Idiopathic osteosclerosis is characterized by being asymptomatic, having no known etiology and no indicated treatment. The most common place where this bone pathology occurs is in the upper jaw and the most prevalent area is the premolar area, although some authors have reported the molar area as the most prevalent for this bone condensation. Currently, there is insufficient research on the placement of dental implants in patients with idiopathic osteosclerosis to determine the insertion torque strength with which implants should be placed for good primary stability in an area with bone condensation.